2022
DOI: 10.1186/s40104-021-00665-0
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of major bioactive dietary nutrients in lamb meat quality: a review

Abstract: Feed supplementation with α-linolenic acid (ALA) and linoleic acid (LA) increases their content in muscle, ALA increases n-3 polyunsaturated fatty acids and decrease n-6/n-3 ratio in muscle, and LA increases rumenic acid. However, high LA supplementation may have negative effects on lambs’ lipid oxidative stability of meat. When the sources of ALA and LA are fed as fresh forage, the negative effects are counterbalanced by the presence of other bioactive compounds, as vitamin E (mainly α-tocopherol) and polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 125 publications
1
15
0
Order By: Relevance
“…However, lamb meat has a low n-6/n-3 ratio compared to other meats, such as pork and chicken (3.7 vs. 6.4 and 5.0, respectively) [ 31 ]. It is also an interesting source of conjugated linoleic acid (CLA), particularly the cis-9, trans-11 isomer (also called rumenic acid), as well as α-linolenic acid (C18:3 n-3) and its elongation products [ 32 ]. Other lipid quality indicators also indicate high nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…However, lamb meat has a low n-6/n-3 ratio compared to other meats, such as pork and chicken (3.7 vs. 6.4 and 5.0, respectively) [ 31 ]. It is also an interesting source of conjugated linoleic acid (CLA), particularly the cis-9, trans-11 isomer (also called rumenic acid), as well as α-linolenic acid (C18:3 n-3) and its elongation products [ 32 ]. Other lipid quality indicators also indicate high nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…What is surprising is that loin‐eye area increased significantly in our study ( P < 0.05), this result has rarely been described in previous. Linseed contains about 56% ALA (Jiménez et al, 2013), it has been reported that feed supplementation with ALA increases their content in muscle, ALA increases the content of n‐3 PUFA in muscle and decreases the ratio of n‐6/n‐3 (Alvarez‐Rodriguez et al, 2022). Li et al (2015) showed that the loin‐eye area increased significantly with the increase of n‐3 PUFA level.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the colour parameters could be also influenced by the increase in oxidation level (TBARS), which in the burgers of group L was higher, due to an abrupt reduction in mitochondrial respiratory activity, which determines a great production of metmyoglobin [38]. A recent review on the effect of bioactive dietary nutrients on meat oxidation and colour stability has shown that in most ruminant studies the greatest colour stability and the least peroxidation were obtained in the meat of animals fed a super-nutritional dose of vitamin E. [39]. Our results also demonstrated for the first time that the oxidative stability and colour measurements of burgers from young Marchigiana bulls could be preserved when a high dosage of vitamin E is added during the finishing period.…”
Section: Discussionmentioning
confidence: 99%